The Question Intent Matrix: A Framework for Interpreting Emotional and Intentional Layers of Questions in Education - Ganga Sudhan (New Zealand Journal of Teachers' Work)
Communication in educational and community contexts often hinges not just on what is asked but why and how it is asked. This article introduces Sudhan’s Question Intent Matrix, a novel 2x2 framework for interpreting the emotional and intentional layers behind questions. The matrix is defined by two axes – Emotional Energy (ranging from defensive, low-openness to curious, high-openness) and Intent (ranging from an intent to influence to an intent to understand) – yielding four quadrants of question types: Curious Questions, Check-in Questions, Challenge Questions, and Control Questions. Grounded in communication theory and pedagogical practice, the model builds on foundational ideas including Speech Act Theory, intent-based communication principles, Socratic questioning, and Edgar Schein’s concept of Humble Inquiry. I propose that by “listening for intent” behind questions, educators and community practitioners can respond more effectively, fostering better understanding, empathy, and critical dialogue. The article details the theoretical underpinnings of the matrix, describes each quadrant of the framework, and discusses its practical implications for enhancing communication and learning in educational and community support settings.